Effects of Lacticaseibacillus casei Zhang addition on physicochemical properties and metabolomics of fermented camel milk during storage - Dandan Wang; Wusigale; Lu Li; Lu Bai; Yongfu Chen (Food Chemistry: X)
Lacticaseibacillus casei Zhang (L. casei Zhang) was used as an auxiliary starter culture to explore its application in camel milk fermentation. This study evaluated the effects of L. casei Zhang supplementation on viable cell count, acidity, texture, insulin-like growth factor 1 (IGF-1) retention, and metabolite profiles over a 21-day storage period. L. casei Zhang enhanced the retention rate of active IGF-1 from 52.95% to 59.13% and mitigated the progression of acidity (from 125 °T to 97.5 °T) compared with the control group. Additionally, L. casei Zhang significantly improved viscosity and promoted the formation of gel structures. Furthermore, its addition significantly influenced the production of key metabolites, including adenosine diphosphate, oleuropein, and threonine–tryptophan (P < 0.05). These findings highlight the potential of L. casei Zhang as an effective auxiliary starter culture for camel milk fermentation, enhancing its physicochemical properties and modulating its metabolomic profile.